1.6 Million transactions replicate distributed PV market slowdown by COVID-19 lockdown. (1st February 2021) - Zhang, Haoran; Yan, Jinyue; Yu, Qing; Obersteiner, Michael; Li, Wenjing; Chen, Jinyu; Zhang, Qiong; Jiang, Mingkun; Wallin, Fredrik; Song, Xuan; Wu, Jiang; Wang, Xin; et al.
Abstract: Solar PV has seen a spectacular market development in recent years and has become a cost competitive source of electricity in many parts of the world. Yet, prospective observations show that the coronavirus pandemic could impact renewable energy projects, especially in the distributed market. Tracking and attributing the economic footprint of COVID-19 lockdowns in the photovoltaic sector poses a significant research challenge. Based on millions of financial transaction records and 44 thousand photovoltaic installation records, we tracked the spatio-temporal sale network of the distributed photovoltaic market and explored the extent of market slowdown. We found that a two-month lockdown duration can be assessed as a high-risk threshold value. When the lockdown duration exceeds the threshold value, the monthly value-added loss reaches 67.7%, and emission reduction capacity is cut by 64.2% over the whole year. We show that risks of a slowdown in PV deployment due to COVID-19 lockdowns can be mitigated by comprehensive incentive strategies for the distributed PV market amid market uncertainties.